Straw and Plastic Mulching Enhances Crop Productivity via Optimizing Interspecific Interactions of Wheat–Maize Intercropping in Arid Areas. Issue 5 (15th August 2019) - Yin, Wen; Fan, Zhilong; Hu, Falong; Fan, Hong; Yu, Aizhong; Zhao, Cai; Chai, Qiang
Abstract : Intercropping is considered as a promising system for improving crop productivity. In arid environments, it is unknown whether the coordinated interspecific interaction can be improved via optimizing agronomic management measures. In this study, we quantified the competitiveness of the intercrops in response to straw and plastic management during both co‐growth periods, and the compensation effect of each intercrop. A late‐maturing maize ( Zea mays L.) was alternately planted in field strips with an early‐maturing wheat ( Triticum aestivum L.) under four straw and plastic management patterns in northwestern China from 2014 to 2016. Intercropped wheat was the dominant species, and the average index of competitiveness of wheat to maize ( A WM ) was 0.403. Integration of straw and plastic mulching application in wheat–maize intercropping reduced the interspecific competition and improved the compensation effect of intercropped maize. On average, no tillage with straw covering the soil in wheat strip combined with 2‐yr plastic mulching in maize strip (i.e., NTSI2) decreased the A WM by 30.9%, increased the growth rate of the intercropped maize by 23.4%, boosted grain yield of intercropped wheat and maize by 9.7 and 17.6%, and boosted total grain yields by 14.9% compared with the conventional intercropping treatment (i.e., CTI). The grain yields of intercrops are a quadratic regression with A WM, and A WM values of 0.354 to 0.375 are the most beneficial to boost the grain yields of the intercropped components. The NTSI2 treatment provided the greatest benefits for weakening the relative competitiveness of the intercrops while strengthening the compensation effect, and boosting the productivity of a wheat–maize intercropping pattern.